Nitrogen Efficiency in Agriculture in Europe and India - Klaas W. Van der Hoek (The Scientific World Journal)
Nitrogen balance sheets are useful tools for studying the quantitative aspects of nutrients. Nitrogen balance sheets have been prepared for the animal production system, crop production system, and for the agricultural sector as a whole for all 15 member states of the European Union (EU15) and for the Indian subcontinent. The EU15 and India were chosen for this study on nitrogen efficiency using balance sheets because they each occupy roughly 300 million ha of land and use about 65 kg nitrogen fertiliser per hectare of agricultural land. Balance sheets were constructed for three systems: animal production, crop production, and the agricultural sector as a whole. In addition to detailed descriptions of the nitrogen balance sheets, brief recommendations for reducing nitrogen surpluses are also given. Surprisingly, the balance sheets for crop production and the agricultural sector as a whole showed a surplus of about 60 kg of nitrogen per hectare of agricultural land.